The Australian universities: A study in public policy failure - Frank Milne (Queen's University, Department of Economics, 2001)
Over the last decade and a half, the Australian Universities have been subjected to a series of reforms introduced by the Australian Commonwealth Government. This paper discusses these reforms, subsequent policy changes, and their impact on the Australian university system. I will argue that the experience has been a disaster and will have long-term adverse effects on the Australian universities, the faculty, the education of university graduates and a detrimental, long term impact on the Australian economy and society. Not all the reforms were ill-judged: a few of the changes imposed on the system were sensible ideas, but the overall impact has been to diminish the quality of the university system and lead to a serious brain drain of quality academics.
Keywords: I21; I23; I28; 330; Australia; Higher Education Policy Failure; Universities; Bildungspolitik; Hochschulreform; Bildungsniveau; Volkswirtschaft; Australien